Clinicians’ Knowledge, Attitudes, and Practices Regarding Infections with Multidrug-Resistant Gram-Negative Bacilli in Intensive Care Units - Zhou, Juyan Julia (Infect Control Hosp Epidemiol, 2013)
OBJECTIVE: To assess how healthcare professionals caring for patients in intensive care units (ICUs) understand and use antimicrobial susceptibility testing (AST) for multidrug-resistant gram-negative bacilli (MDR-GNB). DESIGN: A knowledge, attitude and practice survey assessed ICU clinicians knowledge of antimicrobial resistance, confidence interpreting susceptibility testing, and beliefs regarding the impact of susceptibility testing on patient outcomes. SETTING: 16 ICUs affiliated with New York-Presbyterian Hospital. PARTICIPANTS: Attending physicians and subspecialty residents with primary clinical responsibilities in adult or pediatric ICUs and infectious diseases (ID) subspecialists and clinical pharmacists. METHODS: Participants completed an anonymous electronic survey. Responses included 4-level Likert scales dichotomized for analysis. Multivariate analyses were performed using Generalized Estimating Equations logistic regression to account for correlation of respondents from the same ICU. RESULTS: The response rate was 51% (178/349 eligible participants) of whom 120 (67%) were ICU physicians. Those caring for adult patients were more knowledgeable about antimicrobial activity and more familiar with MDR-GNB infections. Only 33% and 12% of ICU physicians were familiar with standardized and specialized AST methods, respectively, but >95% believed AST improved patient outcomes. When adjusted for demographic and healthcare provider characteristics, those familiar with treatment of MDR-GNB bloodstream infections, those aware of resistance mechanisms, and those aware of AST methods were more confident they could interpret AST and/or request additional in vitro testing. CONCLUSIONS: Our study uncovered knowledge gaps and educational needs that could serve as the foundation for future interventions. Familiarity with MDR-GNB increased overall knowledge and familiarity with AST increased confidence interpreting these results.